On some specific aspects of teaching versatile translation at higher educational establishments - Чернуха, Ірина Андріївна; Рожкова, Марія Геннадіївна (Київський національний університет імені Тараса Шевченка, 2021)
The general theory of translation is an interdisciplinary area, predominantly linguistic but also closely allied to psychology, ethnography, area studies, etc. It is based on the application of linguistic theory to a specific type of speech behavior, i.e. translation. Translation has a subject-matter of its own (the process of translation) and uses the data of contrastive linguistics merely as a point of departure. Translation may be viewed, as an interlingual communicative act in which at least 3 participants are involved: the sender of source information (the author of the SL message), the translator who acts in dual capacity – as the receptor of SL message and as the sender of the equivalent TL message and the receptor of the TL message (translation). In producing the TL text the translator changes its plan of expression (linguistic form) while its plan of content (meaning) should remain unchanged. That means, above all, that whatever the text says and whatever it implies should be understood in the same way by both the SL user for whom it was originally included and by the TL user. It is therefore the translator's duty to make available to the TL receptor the maximum amount of information, carried by linguistic signs, including both their denotational (referential) meanings (i.e. information about the extralinguistic reality which they denote) and their emotive-stylistic connotation. The Ukrainian legal terms such as післядипломна освіта "postgraduate education" and дошкільна освіта "preschool education" are both construed by means of affixation, or pre-fixation, to be more accurate.

Загальна теорія перекладу є переважно лінгвістичною міждисциплінарною сферою, тісно пов'язаною з психологією, етнографією, країнознавством тощо. Вона базується на застосуванні лінгвістичної теорії до спеціального типу мовної поведінки, тобто перекладу. Переклад має власну тему (процес перекладу) та використовує дані контрастивної лінгвістики всього лише у якості своєї відправної точки. Переклад можна розглядати як міжмовний комунікативний акт, у якому залучено щонайменше три учасники: відправник інформації-джерела, перекладач, який виступає і у якості одержувача інформації-джерела, і як відправник еквівалентного повідомленняцільової мови, тобто перекладу. Відтворюючи тест цільової мови, перекладач змінює його план вираження (лінгвістичну форму), а план змісту (значення) має залишитися незмінним. Це означає, перш за все, що будь-який текст повинен бути зрозумілий і сприйнятий однаковою мірою як відправником інформації-джерела, так і одержувачем такої інформації. Таким чином, завданням перекладача єпередача одержувачу інформації-джерела за допомогою лінгвістичних знаків, включаючи як денотативне значення (тобто інформацію про екстралінгвістичну реальність, яку вони позначають), так і їх емоційно-стилістичну конотацію. Все це повною мірою стосуєтьсявикладання англійської як мови для спеціальних цілей. У статті наголошено на дефінітивній логіці розрізнення професійних термінів 'післядипломна освіта' / 'postgraduate education' та 'дошкільна освіта' / 'preschool education', що неоднозначно сприймаються у світовому науковому контексті.
Про деякі особливі аспекти навчання універсального перекладу у вищих навчальних закладах
Keywords: translation; analysis; interdisciplinary; subject-matter; correspondence; linguistic; message; extralinguistic; LSP-teaching; practitioner.; переклад; аналіз; міждисциплінарний; власна тема; відповідність; лінгвістичний; екстралінгвальний; повідомлення; викладач-практик; викладання мови для спеціальних цілей.